2021
DOI: 10.1021/acs.jpca.1c03817
|View full text |Cite
|
Sign up to set email alerts
|

Proximity Effects of Substituents on Halogen Bond Strength

Abstract: It is well known that the presence of an electron-withdrawing substituent (EWS) placed near the halogen (X) atom on a Lewis acid molecule amplifies the ability of this unit to engage in a halogen bond with a base. Quantum calculations are applied to examine how quickly these effects fade as the EWS is moved further and further from the X atom. Conjugated alkene and alkyne chains of varying lengths with a terminal C−I first facilitate analysis as to how the number of these multiple bonds affects the strength of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 79 publications
3
22
0
Order By: Relevance
“…Unlike most of the other properties, this coupling constant is considerably larger for T1 than for T2. It should be pointed out finally that these various spectral changes are not unique to the FX dimers examined here but are general features of halogen bonds in general and even occur in complexes containing closely related interactions such as chalcogen and pnicogen and even hydrogen bonds. , …”
Section: Discussionmentioning
confidence: 79%
“…Unlike most of the other properties, this coupling constant is considerably larger for T1 than for T2. It should be pointed out finally that these various spectral changes are not unique to the FX dimers examined here but are general features of halogen bonds in general and even occur in complexes containing closely related interactions such as chalcogen and pnicogen and even hydrogen bonds. , …”
Section: Discussionmentioning
confidence: 79%
“…This expectation has indeed been confirmed, as in the ChemPhysChem multiple F-substitution [82] on iodobenzene, or in another work where two F or CN substituents were added to iodobenzene. [30] The latter set of computations found that this disubstitution was additive in the sense that the effects of two groups were nearly precisely double that of a single such substituent.…”
Section: Discussionmentioning
confidence: 94%
“…The deshielding of the N atom is consistent with earlier studies of related systems, as well as its linear relationship to bond strength. [10,30,72,73] It is intriguing to note that in contrast to the drop of the shielding around the electron donor N atom here, the opposite effect of an increase in [a] Values for R=H: N À 12.0, I À 115.9, C À 6.7 ppm. shielding accompanies the formation of a noncovalent bond to the O atom of N-methylacetamide.…”
Section: Nmr Spectramentioning
confidence: 93%
See 2 more Smart Citations